Diagnostic Value of Neutrophil to Lymphocyte Ratio in Evaluation of Inflammation in CKD Patients (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Neutrophil to Lymphocyte Ratio (NLR) may be a useful and less costly marker in relation to other tests for identifying inflammation in patients with chronic kidney disease at high risk of Cardiovascular Disease (CVD)-related complications. To evaluate the NLR as inflammatory marker among the CKD patients.  Material and methods: This is a cross-sectional analytical study was conducted in Chittagong Medical College Hospital during the period of May 2019 to May 2020. Eligible participants were patients of pre- dialysis and haemodialysis CKD patients. Total study duration was one year. Clinical data was obtained from patients through interviews. Complete blood count, serum creatinine, serum albumin, fasting lipid profile and C-Reactive Protein (CRP) were measured. NLR were constructed by dividing neutrophil count to lymphocyte count.  Results: Regarding socio-demographic variables, most of the patients were at age group 40-60 years (55.3%) and most were male (75.3%). 46 (54.1%) patients came from rural setting. Among all patients, 84 (98.8%) were hypertensive, (52.9%) were diabetic, 62 (72.9%) patients were at CKD stage 5 and 62 (72.9%) were on dialysis. Among all, 37 (73%) cases of CKD were due to DM, 26 (30.6%) were due to HTN and 18 (21.2%) were due to GN. NLR was raised in 57 (67.1%) cases, and hs-CRP was found raised in 61 (71.8%) cases. There is no relation with age, gender and residence ration of NLR level among CKD patients. There are no significant association of NLR with HTN, DL and IHD but presence of DM is significantly (p